Boom city! Regional resource peripheries and urban economic development in Chile. Issue 3 (2nd July 2020) - Rehner, Johannes; Murray, Warwick E.; Rodriguez, Sebastián; Overton, John
ABSTRACT: Although most studies of resource peripheries are macroeconomic in scale, a regional perspective permits a better understanding of the economic implications of commodity dependence. This study of the boom in commodity exports in Chile in the period 2005–15 shows that while a boom may have adverse effects on other activities, it also had positive impacts on the demand for 'non-tradable' construction, commerce and hospitality services in urban areas through the investment of economic rents and expansion of the secondary circuit of capital. These impacts differed significantly between booming and non-booming cities, leading to a call for rescaling, spatializing and temporalizing research on resource peripheries.